Medizinische Gutachten des 17. und 18. Jahrhunderts Sprachhistorische Untersuchungen zu einer Textsortenklasse - Lindner , Bettina (Lingua Academica, 2018)
Historical text species research is still a relatively unexplored field for German, and so far only a few historical text types have been recorded and described. With the medical reports, this study focuses on a historical text class, which was of central importance for medical communication as early as the 17th and 18th centuries. Starting point of the investigation are common, present-oriented textlinguistic description approaches that are modified for language-historical contexts and extended by important pragmatic categories. The greater consideration of meta-communicative knowledge inventories, as manifested in rhetoric textbooks, text-type guides and text-type designations, has proven particularly fruitful. On the basis of this broad analysis model, the respective text types - Consilia, court reports and section reports - are examined and described in terms of cultural and historical science as well as with regard to the linguistic characteristics typical for them. The study thus offers not only language and medical historians but also cultural scientists an interesting insight into the medical specialist communication of the time.